How much will it hurt? HPV vaccine side effects and influence on completion of the three-dose regimen - Reiter, Paul L. (2009)
We examined the prevalence of reported pain following human papillomavirus (HPV) vaccination and whether it differed from that for other adolescent vaccines or affected completion of the HPV vaccine regimen. In 2008, we conducted cross-sectional surveys with parents of adolescent girls aged 11–20 living in areas of North Carolina with elevated cervical cancer rates who had received at least one dose of HPV vaccine. Pain from HPV vaccination, while commonly reported by parents, was less frequent compared to other adolescent vaccines and did not appear to affect vaccine regimen completion. These findings may be important to increase HPV vaccination coverage.